2014
DOI: 10.1177/1477153514548089
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual responses to LED illumination with colour rendering indices of 85 and 97

Abstract: A light source's ability to render colours and whites is one aspect of lighting quality. Since better colour rendition generally comes with a penalty in luminous efficacy, it is reasonable to consider the balance: Should colour and whiteness rendition be sacrificed to achieve higher efficacy? Here, we investigate perceptual responses under illumination from two sources, a blue-pumped LED with a colour rendering index of 85 (BLED85), and a violet-pumped LED with a colour rendering index of 97 (VLED97). Forty-ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 26 publications
(37 reference statements)
1
49
0
Order By: Relevance
“…It can be observed that the color differences with the GW algorithm were similar for all the patches; while those with the RM varied a lot. Though the FWA excitation created blue tints and produced blue shifts, the largest color differences with the RM algorithm not only happened to bluish patches (e.g., Patches 7,12,17,19,20,and 22) but also to the neutral patches (e.g., Patches 5 and 6). The comparisons of the balanced B values (i.e., B 0 ) of each patch between these two pairs of images, as shown in Figure 14, suggest that the color differences caused by the 14 the results clearly revealed that the failure of blue-pumped white LEDs in rendering FWAenhanced whites can cause noticeable color difference not only to human perception of white appearance of surface colors, but also to the appearance of various colors produced by imaging systems using white balance algorithms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that the color differences with the GW algorithm were similar for all the patches; while those with the RM varied a lot. Though the FWA excitation created blue tints and produced blue shifts, the largest color differences with the RM algorithm not only happened to bluish patches (e.g., Patches 7,12,17,19,20,and 22) but also to the neutral patches (e.g., Patches 5 and 6). The comparisons of the balanced B values (i.e., B 0 ) of each patch between these two pairs of images, as shown in Figure 14, suggest that the color differences caused by the 14 the results clearly revealed that the failure of blue-pumped white LEDs in rendering FWAenhanced whites can cause noticeable color difference not only to human perception of white appearance of surface colors, but also to the appearance of various colors produced by imaging systems using white balance algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…14 Typical blue-pumped white LEDs that are gradually becoming dominant in general illumination, however, contain little violet or ultraviolet radiation, 14,15 which has been found to affect significantly the whiteness appearance of surface colors perceived by humans. [16][17][18] Though FWA excitation plays an important role in the color appearance of white surfaces, its impact on white balance algorithms has never been investigated. In this study, a setup containing a Macbeth ColorChecker and one of three diffuse acrylic whiteness standards with different amount of FWAs was captured under four illuminants having different levels of CCT and UV/violet radiation, with a goal to investigate the impact of FWA excitation on white balance algorithms.…”
Section: Color Appearance Of White Surfaces and White Balance Algormentioning
confidence: 99%
“…3. The change of the gamut shape was purposely designed, because both red and green were dominant colors in the painting and past studies have clearly suggested the important role of red in color preference evaluations Wei, Houser, Allen, and Beers 2014;Wei, Houser, David, and Krames 2014). All of the light settings were designed to be metameric, with a correlated color temperature (CCT) of 3000 K and a D uv of −0.005.…”
Section: Light Settings and Observers' Evaluationsmentioning
confidence: 99%
“…Most psychophysical experiments investigating color preference, including those described above, were conducted under a single illuminance level between 200 and 500 lx (Islam et al 2013;Jost-Boissard et al 2009Lin et al 2014Lin et al , 2015Liu et al 2013;Ohno et al 2015;Rea and Freyssinier 2010;Szabo et al 2014;Teunissen et al 2016;Veitch et al 2014;Houser 2016, 2017;Wei, Houser, Allen, and Beers 2014;Wei, Houser, David, and Krames 2014;. Such a range not only ensured that the illuminance was within the range of photopic vision but also covered most of the recommended illuminance levels for general illumination (DiLaura et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Such problems are particularly solved by replacement of blue LED chip by violet one, following two phosphors technology [15,16]. Unfortunately the authors have any such light source for disposal during presented experiment.…”
Section: Methodsmentioning
confidence: 99%